2005
DOI: 10.1021/jp040503h
|View full text |Cite
|
Sign up to set email alerts
|

Product Channels of the HCCO + NO Reaction

Abstract: The product branching ratio of the HCCO + NO reaction was investigated using the laser photolysis/infrared absorption technique. Ethyl ethynyl ether (C(2)H(5)OCCH) was used as the HCCO radical precursor. Transient infrared detection of CO, CO(2), and HCNO products was used to determine the following branching ratios at 296 K: phi(CO+HCNO) = 0.78 +/- 0.04 and phi(CO(2)+HCN) = 0.22 +/- 0.04. These values are in good agreement with some recent ab initio calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…has been characterized experimentally in a number of studies [312314,324328] and both the overall rate constant and the branching fraction is fairly well established. Measurements of the branching fraction indicate that the HCNO + CO channel (R91) dominates, with reported yields of 64-88% [313,314,326,327]. We have combined the total rate coecient measurement of Carl et al [312] with the reported branching fraction, which appears to be independent of temperature [313,314], to arrive at the rate coecients used in the present work.…”
Section: Reaction Subset For Reburningmentioning
confidence: 97%
“…has been characterized experimentally in a number of studies [312314,324328] and both the overall rate constant and the branching fraction is fairly well established. Measurements of the branching fraction indicate that the HCNO + CO channel (R91) dominates, with reported yields of 64-88% [313,314,326,327]. We have combined the total rate coecient measurement of Carl et al [312] with the reported branching fraction, which appears to be independent of temperature [313,314], to arrive at the rate coecients used in the present work.…”
Section: Reaction Subset For Reburningmentioning
confidence: 97%
“…of Path P 6 . Therefore, the pathway P 6 can proceed much more easily than P 6 , to be considered as a major product channel.…”
Section: Table Imentioning
confidence: 99%
“…The PES in Figure 5 shows that the pathway P 6 takes the common division R → d as starting step Path P 6 : where the CO molecule keeps unchanged in the sub process 1 → P 6 The pathway R(0.0) → e(−27.2) to products P 6 involves a very high-energy transition state f/1 as is therefore not expected to be important. An alternative pathway is suggested: Path P 6 :…”
Section: Pathway P 6 a Major Product Channelmentioning
confidence: 99%
See 2 more Smart Citations